Wennovation Hub agritech incubation program - Odetayo, Wole (Technical Centre for Agricultural and Rural Cooperation, 2018)
Wole Odetayo, from Nigeria, created Wennovation Hub in 2011. he shares his experience on the Agritech incubation program that he has been organising since 2015 .